Customer satisfaction as a reality of health service quality - Tanko Titus Auta; Sanglar Polnok; Fransiskus Salesius Onggang; Keumalhayati Keumalhayati; Arbaiyah Arbaiyah; Nora Hayani; Idwar Idwar (Aloha International Journal of Health Advancement (AIJHA), 2022)
Health care institutions must strive to satisfy customers. The spread of customer complaints should be avoided and instead customer satisfaction should be spread effectively. Satisfied customers usually have high loyalty, which must be maintained rather than chasing other customers who are not necessarily loyal. With the increasingly fierce competition in the global era, customer satisfaction must get serious attention. Every health service provider must try to satisfy customers if it wants to exist in the competition. Keywords: health service; quality; customer satisfaction